Accumulating Attributes (for Doaitse Swierstra‚ on his retirement) - Gibbons, J (2013)
Doaitse has always been enthusiastic about attribute grammars, seeing them even where most people don't. While I was writing up my DPhil thesis, he explained to me where they were in that too. This paper is by way of belated thanks for that perspective - and as a more general rendering of the observation, with the benefit of hindsight and twenty years of progress.